Direct comparison of the in vitro and in vivo stability of DFO, DFO* and DFOcyclo* for (89)Zr-immunoPET - Raavé, René (Eur J Nucl Med Mol Imaging, 2019)
PURPOSE: Currently, the most commonly used chelator for labelling antibodies with (89)Zr for immunoPET is desferrioxamine B (DFO). However, preclinical studies have shown that the limited in vivo stability of the (89)Zr-DFO complex results in release of (89)Zr, which accumulates in mineral bone. Here we report a novel chelator DFOcyclo*, a preorganized extended DFO derivative that enables octacoordination of the (89)Zr radiometal. The aim was to compare the in vitro and in vivo stability of [(89)Zr]Zr-DFOcyclo*, [(89)Zr]Zr-DFO* and [(89)Zr]Zr-DFO. METHODS: The stability of (89)Zr-labelled chelators alone and after conjugation to trastuzumab was evaluated in human plasma and PBS, and in the presence of excess EDTA or DFO. The immunoreactive fraction, IC(50), and internalization rate of the conjugates were evaluated using HER2-expressing SKOV-3 cells. The in vivo distribution was investigated in mice with subcutaneous HER2(+) SKOV-3 or HER2(−) MDA-MB-231 xenografts by PET/CT imaging and quantitative ex vivo tissue analyses 7 days after injection. RESULTS: (89)Zr-labelled DFO, DFO* and DFOcyclo* were stable in human plasma for up to 7 days. In competition with EDTA, DFO* and DFOcyclo* showed higher stability than DFO. In competition with excess DFO, DFOcyclo*-trastuzumab was significantly more stable than the corresponding DFO and DFO* conjugates (p < 0.001). Cell binding and internalization were similar for the three conjugates. In in vivo studies, HER2(+) SKOV-3 tumour-bearing mice showed significantly lower bone uptake (p < 0.001) 168 h after injection with [(89)Zr]Zr-DFOcyclo*-trastuzumab (femur 1.5 ± 0.3%ID/g, knee 2.1 ± 0.4%ID/g) or [(89)Zr]Zr-DFO*-trastuzumab (femur 2.0 ± 0.3%ID/g, knee 2.68 ± 0.4%ID/g) than after injection with [(89)Zr]Zr-DFO-trastuzumab (femur 4.5 ± 0.6%ID/g, knee 7.8 ± 0.6%ID/g). Blood levels, tumour uptake and uptake in other organs were not significantly different at 168 h after injection. HER2(−) MDA-MB-231 tumour-bearing mice showed significantly lower tumour uptake (p < 0.001) after injection with [(89)Zr]Zr-DFOcyclo*-trastuzumab (16.2 ± 10.1%ID/g) and [(89)Zr]Zr-DFO-trastuzumab (19.6 ± 3.2%ID/g) than HER2(+) SKOV-3 tumour-bearing mice (72.1 ± 14.6%ID/g and 93.1 ± 20.9%ID/g, respectively), while bone uptake was similar. CONCLUSION: (89)Zr-labelled DFOcyclo* and DFOcyclo*-trastuzumab showed higher in vitro and in vivo stability than the current commonly used (89)Zr-DFO-trastuzumab. DFOcyclo* is a promising candidate to become the new clinically used standard chelator for (89)Zr immunoPET. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00259-019-04343-2) contains supplementary material, which is available to authorized users.